2015
DOI: 10.1111/adb.12317
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study of body mass index in subjects with alcohol dependence

Abstract: Outcomes related to disordered metabolism are common in alcohol dependence (AD). To investigate alterations in the regulation of body mass that occur in the context of AD, we performed a GWAS of BMI in African-Americans (AAs) and European-Americans (EAs) with AD. Subjects were recruited for genetic studies of alcohol or drug dependence, and evaluated using the Semi-Structured Assessment for Drug Dependence and Alcoholism. We investigated a total of 2,587 AAs and 2,959 EAs with DSM-IV AD diagnosis. In the stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…A Mendelian randomization study in 261 991 individuals of European descent indicated that carriers of the ADH1B rs1229984 protective allele have a more favorable cardiovascular profile (Holmes et al, 2014). Furthermore, our recent GWAS of BMI in subjects with alcohol dependence showed that an alcohol-metabolism gene (in that case, ALDH1A1) could be involved in the regulation of body mass in the context of alcohol dependence (Polimanti et al, 2015b). These findings support a relationship between alcohol-metabolism gene variants with cardiovascular and metabolic conditions.…”
Section: Discussionmentioning
confidence: 55%
“…A Mendelian randomization study in 261 991 individuals of European descent indicated that carriers of the ADH1B rs1229984 protective allele have a more favorable cardiovascular profile (Holmes et al, 2014). Furthermore, our recent GWAS of BMI in subjects with alcohol dependence showed that an alcohol-metabolism gene (in that case, ALDH1A1) could be involved in the regulation of body mass in the context of alcohol dependence (Polimanti et al, 2015b). These findings support a relationship between alcohol-metabolism gene variants with cardiovascular and metabolic conditions.…”
Section: Discussionmentioning
confidence: 55%
“…However, there is very little available information on the molecular mechanisms by which alcohol-related behaviors contribute to RSB. Genomewide analysis can be a powerful tool to identify molecular mechanisms of complex traits, including in the context of alcohol abuse (Polimanti et al, 2015). Although no large genomic investigation has been conducted on RSB, a recent genome-wide association study (GWAS) of age at first sexual intercourse indicated that the onset of sexual activity is genetically correlated to other reproductive and behavioral traits (Day et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we present a supervised ML method (SVM) to classify individuals before AUD emerged into those who developed AUD years later and those who did not. The analysis incorporates EEG measures, FH information, and data on a set of SNPs derived from recent GWAS of alcohol consumption 12,13 , alcohol dependence 14,15 , and alcohol-related EEG measures 15,16 , as features. An essential aspect of identifying a true classifier is to control for possible effects of confounding variables such as age 17,18 , gender 19,20 , and ancestry 21,22 which can lead to misclassification of the model 23 .…”
Section: Introductionmentioning
confidence: 99%